Management of foot rot (Phytophthora capsici) disease of black pepper (Piper nigrum L.) through fungicides and cultural practices in Southwestern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2023)
The pathogen Phytophthora capsici, which causes black pepper foot rot, is the most detrimental disease that affects black pepper productivity and lowers qualitative and quantitative spike yields in southwest Ethiopia. The effectiveness of several fungicides and cultural methods against Phytophthora capsici in black pepper was tested in a field experiment. Five commercial fungicides and cultural practices were examined, and a natural Phytophthora capsici infection was noted. Disease incidence was determined by visually observing leaf blight, spike infection, leaf shedding, and vine yellowing. The most effective fungicide, with a disease incidence of 14.3%, was Koka blue 50 WG (Copper oxychloride) spraying when combined with cultural approaches. More 720 WP (Mancozeb + Cymoxanil), a combination of cultural practices and 19.1% disease incidence, came next. Agro-laxyl 63.5 WP (Metalaxyl + Mancozeb) and Progress 250 EC (Propiconazole 25%) combined with cultural practices were also effective against Phytophthora infection and found better than only cultural practices applied plot and control.Int. J. Agril. Res. Innov. Tech. 13(1): 48-50, June 2023